The First Moment of Azimuthal Anisotropy in Nuclear Collisions from AGS to LHC Energies - Subhash Singha; Prashanth Shanmuganathan; Declan Keane (Advances in High Energy Physics)
We review topics related to the first moment of azimuthal anisotropy (v1), commonly known as directed flow, focusing on both charged particles and identified particles from heavy-ion collisions. Beam energies from the highest available, at the CERN LHC, down to projectile kinetic energies per nucleon of a few GeV per nucleon, as studied in experiments at the Brookhaven AGS, fall within our scope. We focus on experimental measurements and on theoretical work where direct comparisons with experiment have been emphasized. The physics addressed or potentially addressed by this review topic includes the study of Quark Gluon Plasma and, more generally, investigation of the Quantum Chromodynamics phase diagram and the equation of state describing the accessible phases.